2021
DOI: 10.1016/j.celrep.2021.108976
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 prevents endogenous RNAs from triggering a lethal RIG-I-dependent interferon response

Abstract: Highlights d Loss of TDP-43 causes accumulation of immunostimulatory double-stranded RNA (dsRNA) d Immunostimulatory dsRNA comprises RNA polymerase III transcripts d Immunostimulatory dsRNA is detected by RIG-I d Lethality of TDP-43 can be rescued by genetic inactivation of the RIG-I pathway

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…For example, while RIG-I can be stimulated by unedited RNA lacking 6-methyladenosine ( 12 ), it can also be actively antagonized by RNAs containing 5′-monophosphates (5′-p RNAs), which are abundant in healthy cells and therefore represent a gating mechanism to prevent basal activation to self-RNA species ( 32 ). The RNA-binding protein TAR DNA-binding protein 43 has also been reported to prevent accumulation of endogenous RNA species that can activate RIG-I ( 33 ). If SF3B1 modulation increases unedited RNA lacking 6-methyladenosine or in contrast decreases RNAs containing 5′-monophosphates or decreases TAR DNA-binding protein 43 expression, these can also represent mechanisms to induce RIG-I activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while RIG-I can be stimulated by unedited RNA lacking 6-methyladenosine ( 12 ), it can also be actively antagonized by RNAs containing 5′-monophosphates (5′-p RNAs), which are abundant in healthy cells and therefore represent a gating mechanism to prevent basal activation to self-RNA species ( 32 ). The RNA-binding protein TAR DNA-binding protein 43 has also been reported to prevent accumulation of endogenous RNA species that can activate RIG-I ( 33 ). If SF3B1 modulation increases unedited RNA lacking 6-methyladenosine or in contrast decreases RNAs containing 5′-monophosphates or decreases TAR DNA-binding protein 43 expression, these can also represent mechanisms to induce RIG-I activation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence demonstrated that TDP43 is a DNA/RNA-binding protein involved in RNA metabolism including the NOTCH1 mRNA. 24 26 Indeed, silencing of LCETRL3 induced significantly downregulated NOTCH1 expression in both the PC9 and H1299 cells (shL3-1 and shL3-2 vs. shNC; P < 0.05) (Fig. 4 j and k ).…”
Section: Resultsmentioning
confidence: 91%
“…We revealed that lncRNA LCETRL3 can interact with TDP43 protein and suppress degradation of TDP43, an RNA-binding protein that participates in multiple steps of RNA metabolism, including transcription, splicing, and transport of mRNA, as well as miRNA metabolism. 24 TDP43 has been shown to promote growth and metastasis of NSCLC, triple-negative breast cancer, neuroblastoma, hepatocellular carcinoma and melanoma. 35 – 40 Consistently, we found that TDP43 was significantly upregulated in NSCLC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis by RIG-I and MDA5 is mediated through a unique mechanism known as RLR-induced IRF3-mediated pathway of apoptosis (RIPA), during which TRAF2, TRAF6, and a linear ubiquitin chain assembly complex (LUBAC) are recruited to modify IRF3, leading to its subsequent translocation with Bax to mitochondria ( Chattopadhyay et al 2010 , 2016 ). Furthermore, RIG-I-dependent IFN response also promotes RIPK3-mediated necroptosis ( Brault et al 2018 ; Dunker et al 2021 ). In many cases, the activation of inflammasome and cell death programs might either exert a protective role by eliminating the virus-infected cells or facilitate virus dissemination and spread by releasing a large number of virion particles.…”
Section: Introductionmentioning
confidence: 99%